The Transcriptome and Metabolome Reveal Stress Responses in Sulfur-Fumigated Cucumber (Cucumis sativus L.) - Juan Liu (Frontiers Media S.A., 2021)
Sulfur (S) fumigation is a commonly used sterilization method in horticultural facilities against fungal diseases. S fumigation damaged cucumber leaves, although the response mechanism is unclear. This study analyzes the growth, transcriptome, and metabolomic profiles of young and mature leaves, ovaries, and commercial cucumber fruits to decipher the mechanism of cucumber stress response under S fumigation. S fumigation significantly changed the photosynthetic efficiency and reactive oxygen species (ROS) in leaves, but not fruit development, fruit mass, and peel color. Transcriptome analysis indicated that S fumigation strongly regulated stress defense genes. The weighted gene co-expression network analysis revealed that S fumigation regulated ASPG1, AMC1 defense genes, LECRK3, and PERK1 protein kinase. The abscisic acid (ABA)-mediated model of regulation under S fumigation was constructed. Metabolome analysis showed that S fumigation significantly upregulated or downregulated the contents of amino acids, organic acids, sugars, glycosides, and lipids (VIP > 1 and P-value < 0.05). The opposite Pearson’s correlations of these differential metabolites implied that cucumber had different metabolic patterns in short-term and long-term S fumigation. Besides, the elevated levels of proline and triglyceride indicated that stress-responsive mechanisms existed in S-fumigated cucumber. Moreover, the comprehensive analysis indicated that S fumigation elevated secondary S-containing metabolites but decreased sulfate absorption and transportation in cucumber. Overall, our results provided a comprehensive assessment of S fumigation on cucumber, which laid the theoretical foundation for S fumigation in protected cultivation.